Persistent Mullerian Duct Syndrome (PMDS) Presenting as a Malignant Tumour - Islam, Md Rafiqul; Ali, Md Showkat; Azam, SM Golam (Medicine Today, 2018)
Persistent Mullerian duct syndrome is a condition in which there is presence of Mullerian duct structures (uterus, fallopian tube, vagina etc.) in an otherwise phenotypically, as well as genotypically, normal man. This patient usually presents with unilateral or bilateral cryptorchidism associated with inguinal hernia and ectopic testis. There is the chance of developing malignancy in ectopic testis (incidence being 15%), as well as infertility in case of bilateral cryptorchidism. Our patient suffers from PMDS presents with malignant tumour. The aim of the presentation of this case is to draw the attention in case of unilateral or bilateral cryptorchidism associated with or without inguinal hernia; the possibility of PMDS should be kept in mind to prevent infertility as well as malignancy. Medicine Today 2018 Vol.30(1): 38-40